Ethnicity and glycaemic control are major determinants of diabetic dyslipidaemia in Malaysia - Ismail, I.S.; Nazaimoon, W.; Mohamad, W.; Letchuman, R.; Singaraveloo, M.; Hew, F.L.; Shuguna, C.; Khalid, B.A.K. (2001)
Aims To define the prevalence of dyslipidaemia in young diabetic patients in Peninsular Malaysia and the contributory factors of dyslipidaemia in these subjects. Methods This is a cross-sectional study involving 848 young diabetic patients from seven different centres, with representation from the three main ethnic groups. Clinical history and physical examination was done and blood taken for HbA(1c), fasting glucose, total cholesterol, low-density lipoprotein (LDL) and high-density lipoprotein (HDL) cholesterol and triglycerides. Results The overall lipids were suboptimal, worse in Type 2 diabetes mellitus (DM) patients compared with Type 1 DM patients. Of the Type 2 patients, 73.2 had total cholesterol > 5.20 mmol/l, 90.9 had LDL-cholesterol > 2.60 mmol/l, 52.6 had HDL-cholesterol < 1.15 mmol/l and 27.3 had serum triglycerides > 2.30 mmol/l. There were ethnic differences in the lipid levels with the Malays having the highest total cholesterol (mean 6.19 mmol/l), and the highest LDL-cholesterol (mean 4.16 mmol/l), while the Chinese had the highest HDL-cholesterol (geometric mean 1.24 mmol/l). Ethnicity was an important determinant of total, LDL- and HDL-cholesterol in Type 2 DM, and LDL- and HDL-cholesterol and triglycerides in Type 1 DM. Glycaemic control was an important determinant of total, LDL-cholesterol and triglycerides in both Type 1 and Type 2 DM. Waist-hip ratio (WHR) was an important determinant of HDL-cholesterol and triglycerides in both types of DM. Gender was an important determinant of HDL-cholesterol in Type 2 DM, but not in Type 1 DM. Socioeconomic factors and diabetes care facilities did not have any effect on the dyslipidaemia. Conclusions The prevalence of dyslipidaemia was high especially in Type 2 DM patients. Ethnicity, glycaemic control, WHR, and gender were important determinants of dyslipidaemia in young diabetic patients.